First Record of Lamprigera tenebrosa (Walker, 1858) Subfamily Lampyrinae from Doon Valley, Uttarakhand, Western Himalaya, India - Rana, Nidhi; Uniyal, V. P.; Rayal, Rajesh (Indian Forester, 2024)
No Abstract.